A novel treatment for esophageal lesions following atrial fibrillation ablation. (5th February 2021) - Rivarola, Esteban W. R.; Moura, Eduardo; Chou, Marco; Feitosa Seabra, Luciana; Hardy, Carina; Scanavacca, Mauricio
Abstract: This study presents a novel technique for the treatment of a deep esophageal ulcer after ablation of paroxysmal atrial fibrillation (AF). Pulmonary vein isolation was performed using a radiofrequency irrigated tip catheter. On Day 5 of follow‐up, a deep esophageal ulcer was observed. No significant visual improvement was observed after conventional treatment. Endoscopic negative pressure therapy in the esophagus was then applied for 5 days. A significant decrease in diameter and depth of the lesion was observed, possibly preventing perforation. Endoscopic negative pressure therapy can be used to heal thermal lesions after AF ablation procedures.